2017
DOI: 10.1371/journal.pone.0183467
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between parenting stress and informant discrepancies on symptoms of ADHD/ODD and internalizing behaviors in preschool children

Abstract: Parent and teacher ratings of child behaviors are often discrepant, and these discrepancies may be correlated with parenting stress. The present study explored whether various parenting stress factors are associated with discrepancies between parent and teacher ratings of attention-deficit/hyperactivity disorder and oppositional defiant disorder (ODD) as well as internalizing symptoms in preschool children. We recruited 299 Taiwanese preschool children (aged 4–6 years) from the community or via clinical referr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 66 publications
1
15
0
Order By: Relevance
“…To our knowledge, other studies of food insecurity and ADHD in youths have been cross-sectional, 8 and most have relied on maternal reports of ADHD. Maternal ratings of ADHD may be influenced by parental distress, 39 , 40 , 41 which may be associated with food insecurity, 42 , 43 thus possibly inflating observed associations between food insecurity and ADHD. In the current investigation, the use of adolescent ratings probably mitigated the association of parental distress with outcome measurements.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, other studies of food insecurity and ADHD in youths have been cross-sectional, 8 and most have relied on maternal reports of ADHD. Maternal ratings of ADHD may be influenced by parental distress, 39 , 40 , 41 which may be associated with food insecurity, 42 , 43 thus possibly inflating observed associations between food insecurity and ADHD. In the current investigation, the use of adolescent ratings probably mitigated the association of parental distress with outcome measurements.…”
Section: Discussionmentioning
confidence: 99%
“…42 Studies have reported that the Chinese version of the PSI-SF is a reliable assessment tool for identifying parenting stress with a need for intervention in clinical practices. [43][44][45]…”
Section: Cal Assessmentmentioning
confidence: 99%
“…The three sub-scores are added together to yield a total parenting stress score [41]. Studies have reported that the Chinese version of the PSI-SF is a reliable assessment tool for identifying parenting stress with a need for intervention in clinical practices [42][43][44].…”
Section: Parenting Stressmentioning
confidence: 99%